Physicochemical Analysis and Sensory Evaluation of Barley Tea Supplemented with Lemon and Honey - Mohd Nor, Shahirah Amirah; Shakila Abdullah, (Enhanced Knowledge in Sciences and Technology, 2024)
Infusion tea such as Barley Tea addition with other ingredient like lemon and honey, addresses the rising global demand for a healthful barley-based beverage. Therefore the main goals of this study are to assess the effects of supplementing barley tea with different formulation of lemon and honey, investigate physicochemical effects, and examine organoleptic properties. 5 comprehensive formulation evaluations, which include roasting at 240°C for 15 minutes, steeping in water at 100°C for 10 minutes, and adding 11.5g of lemon or 13.5g of honey after chilling to 31°C, reveal favourable sensory reactions with an average total attribute score of 6.84±1.557, scored by 50 untrained panelists. Formulation 4, enhanced with a significant amount of honey, is the best choice due to having a balanced sweetness and sourness. Formulation 2 with honey has great physicochemical characteristics, such as low turbidity (222.000±2.000), high sugar content (7.797±0.015 TSS Brix), and a beverage-safe pH (4.640±0.0). Following analyses, which employ GC-MS to study volatile chemicals, it is determined that esters and aldehydes are common in Formulations 3 and 4, which contributes to their unique flavour and odour profiles. Furthermore, using ATR-FTIR for organic component analysis reveals that the two most common organic compounds in all formulations are amines and alcohol. This study highlights the best effects of supplementing barley tea with lemon and honey on its physicochemical qualities while also improving its sensory qualities and providing insightful information on the nutritious and marketable profile of the beverage. These results have important effects for the beverage sector and offer a novel way to boost the appeal of barley tea by adding lemon and honey.